Sovereign wealth fund investments and the US political process - Calluzzo, Paul; Nathan Dong, G; Godsell, David (Journal of International Business Studies, 2017)
We examine US firm-level campaign finance contributions preceding and subsequent to equity investment by a sovereign wealth fund (SWF). Our empirical results suggest that SWFs are attracted to firms engaged in US campaign finance and that firm campaign finance contributions increase after SWF investment. SWF attraction to campaign finance firms increases (1) after an exogenous legal shock that liberalized corporate campaign finance activities, and (2) in a subset of industries vulnerable to recent legislation capable of inhibiting or expunging foreign investment. We provide some of the first evidence consistent with political motives for SWF investment in the United States.